PENINGKATAN KOMPETENSI PELAKU UMKM DALAM STRATEGI BRANDING BERBASIS TEKNOLOGI - Sandy Suryady; Wisnu Sukma Maulana; Tati Noviati; Nia Yuningsih (Asosiasi Dosen Muda Indonesia, 2024)
This community service program aims to provide training and guidance for Micro, Small, and Medium Enterprises (MSMEs) in implementing technology-based branding strategies. The activity is a collaboration between Gunadarma University and the Indonesian Young Lecturers Association (ADMI), conducted throughout the PTA 2024-2025 academic year. The program employs a hybrid implementation method (online and offline), tailored to the needs of MSMEs. The primary focus of this program is to enhance MSMEs’ understanding and skills in utilizing technology for digital branding, covering creative content creation, social media utilization, and market target analysis using digital tools. This initiative involves six fields of study—Accounting, Management, Industrial Engineering, Mechanical Engineering, Information Systems, and English Literature—to provide a comprehensive interdisciplinary approach. The expected outcomes include improving MSMEs' competencies in building a strong brand identity, managing digital branding campaigns, and expanding market reach through technology. Program outputs include journal publications, activity documentation in the form of videos, and increased lecturer participation. All program results will be reported to Gunadarma University’s Community Service Institution (LPM-UG) as part of program evaluation.